Understanding Users' Perspectives of Psychosocial Mechanisms Underpinning Peer Support Work in Chile. - Le, PhuongThao D.; Agrest, Martín; Mascayano, Franco; Dev, Saloni; Kankan, Tanvi; Dishy, Gabriella; Tapia-Muñoz, Thamara; Tapia, Eric; Toso-Salman, Josefina; Pratt, Charissa; Alves-Nishioka, Silvia; Schilling, Sara; et al. (Community Mental Health Journal, 2022)
This study explores the beliefs and attitudes about the psychosocial mechanisms of peer support work among users who participated in Critical Time Intervention-Task Shifting (CTI-TS), which tested the acceptability and feasibility of a peer support work model to improve community-based mental health care for individuals with psychosis in Latin America. We conducted a secondary analysis of 15 in-depth interviews with CTI-TS participants in Chile, using the framework method and defined the framework domains based on five major mechanisms of peer support work identified by a recent literature review. The analysis revealed that users' perceptions of peer support work mechanisms were strongly shaped by personal motivations, beliefs about professional hierarchies, familial support, and the Chilean mental health system's incipient recovery orientation. The findings underscore the importance of adopting culturally tailored strategies to promote peer support work, such as involving mental health professionals and fostering equal-powered relationships between PSWs and users.